Novel pectin/chitosan Mo-MOF hydrogel for dye adsorption and pathogenic bacteria inhibition - Ghnim, Zahraa Sabah; Adhab, Ayat Hussein; Altalbawy, Farag M. A.; Salih Mahdi, Morug; Salah Mansoor, Aseel; Radi, Usama Kadem; Saadoun Abd, Nasr; Abdul-Reda Hussein, Uday; Hussain Hamza, Hadil; Muzammil, Khursheed; Alkhayyat, Ahmad (Frontiers in Materials, 2025)
This study includes the synthesis of new hydrogel using pectin, chitosan, and Mo-MOF (pectin/chitosan Mo-MOF hydrogel). After confirming the structure of the synthetic hydrogel by Elemental Analysis (EA), Energy-Dispersive X-ray Spectroscopy (EDS), EDS mapping, Fourier-transform infrared spectroscopy (FT-IR), X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM), its application in wastewater treatment, including the absorption of Congo red and the inhibition of pathogenic bacterial strains in wastewater, was evaluated. The factors affecting the adsorption of Congo red, such as pH, temperature, and contact time, were studied. The highest adsorption rate was determined to be 93% using 0.06 g/L of pectin/chitosan Mo-MOF hydrogel under conditions including pH 8, temperature of 25°C, and contact time of 90 min. The microbiology evaluations of the pectin/chitosan Mo-MOF hydrogel, which were performed against the known strains of wastewater such as Campylobacter jejuni, Shigella dysenteriae, Vibrio cholerae, Yersinia enterocolitica, and Salmonella enterica, indicated its high antibacterial properties, so, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values were observed between 4 and 32 μg/mL and 8–64 μg/mL. The diverse characteristics of the pectin/chitosan Mo-MOF hydrogel can be attributed to its physical and chemical properties, such as its constituent compounds, specific surface area, and porosity. Finally, the pectin/chitosan Mo-MOF hydrogel can be introduced as a functional composition with unique capabilities in controlling pathogenic bacterial strains of wastewater and absorbing dangerous chemical compounds of wastewater for environmental purposes.